Design of Concept Art and 2D Frame by Frame Animation in the Animation 'Spectrum Rise’ - Antris, Ardhia Gagas Dhaifullah; Sheanny Ocmi Sakti (The Future of Education Journal, 2025)
This project addresses the issue of low literacy rates in Indonesia, highlighting the need for creative approaches to foster reading interest. An animation titled "Spectrum Rise" was developed as an educational medium by introducing storybooks in an engaging way. The project was carried out using the Multimedia Development Life Cycle (MDLC) method, which includes the stages of concept, design, material collection, assembly, testing, and distribution. The concept art was designed using a clean line art approach adapted to simple characters, supporting production efficiency. The 2D frame-by-frame animation technique was chosen for its ability to provide expressive control over character movements and maintain visual consistency with the script and concept art. The software used includes Toon Boom Harmony for the 2D frame-by-frame animation and Photoshop for the concept art. The final result shows that the integration of concept art and frame-by-frame techniques can produce expressive and efficient animation capable of delivering strong moral messages. With this approach, "Spectrum Rise" is expected to serve as an example of how powerful visual storytelling can be used as an effective tool for social communication.